2023
DOI: 10.3390/antibiotics12050874
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticle Targets Fabricated Using Chemical Vapor Deposition Method for Differentiation of Bacteria Based on Lipidomic Profiles in Laser Desorption/Ionization Mass Spectrometry

Abstract: The global threat of numerous infectious diseases creates a great need to develop new diagnostic methods to facilitate the appropriate prescription of antimicrobial therapy. More recently, the possibility of using bacterial lipidome analysis via laser desorption/ionization mass spectrometry (LDI-MS) as useful diagnostic tool for microbial identification and rapid drug susceptibility has received particular attention because lipids are present in large quantities and can be easily extracted similar to ribosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…S9–S16 ). This aligns with previous investigation of our research group 44 , where silver nanostructured substrates enabled classification of the Escherichia coli strains into cefotaxime-resistant and cefotaxime-sensitive strains, while signals attributed to organic matrix hampered classification in case of application of MALDI.…”
Section: Resultssupporting
confidence: 91%
“…S9–S16 ). This aligns with previous investigation of our research group 44 , where silver nanostructured substrates enabled classification of the Escherichia coli strains into cefotaxime-resistant and cefotaxime-sensitive strains, while signals attributed to organic matrix hampered classification in case of application of MALDI.…”
Section: Resultssupporting
confidence: 91%
“…The significant advantage of the proposed MALDI approach is that information about fatty acids composition is also provided; however, without the need of using a multistep protocol required when gas chromatography (the most traditional and old technique) is applied, which involves saponification of bacterial cells in sodium hydroxide, methylation with hydrochloric acid, lipid extraction, and a wash at a basic pH which typically takes several hours . The powerful impact of the MALDI approach in the differentiation of the bacteria based on their lipidomic profiles, even at the strain level, has been recently proven for E. coli strains isolated from DFI wounds that differed in beta-lactams antibiotic resistance level …”
Section: Resultsmentioning
confidence: 99%
“…In order to confirm the usefulness of such lipid enrichment profile in identifying a phenotype derived from DFI bacteria, further studies would be necessary to compare paired bacterial species colonizing non-DFI wounds. Recent studies showed that 2 h of incubation in the presence of antibiotic (cefotaxime in that case) is enough to detect distinctive lipid patterns of beta-lactam-resistant and -sensitive E. coli strains …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, considering the nature of our investigation into closely related species classification, it is worth noting that the analysis of the lower m/z range (up to m/z 2000) not only pertains to small peptides, as initially discussed, but also encompasses lipids. While our study primarily employed proteomics and genomics approaches, it is crucial to acknowledge that there exists a third option, namely MALDI lipidomics, which can offer valuable insights into the composition and variations of lipids within the studied strains 46 , 47 . This additional dimension of analysis could provide further support for the reliable classification of closely related species and enhance the comprehensiveness of our findings.…”
Section: Discussionmentioning
confidence: 99%